Os gessos e a imagem em movimento : aparições - Taveira, Rogério (2023)
This study focuses on the hypothesis that the field of the moving image could establish itself as an operative system for the production of “problematic”, unstable and open images, based on a dialectic of negatives made from plaster objects in the collection of the Faculty of Fine Arts from the University of Lisbon. From guided tours of gypsotheques illuminated by torches, to the introduction of photography and cinema as a dialectical hypothesis of the future to question the past from the common condition established by the negative, we proceed with a progression of references that were at the origin of our experimental film, Duplo Negativo/Double Negative. The possibility of having “apparitions” as moments of synthesis aims to be the result of that central use in chain of double negatives in luminous metamorphosis